Preparation and Mimic Enzyme Catalytic Kinetics of Dendritic Copper Complex - Wang, Jun; Yang, Guang; Li, Cuiqin; Zhangi, Peng (Asian Journal of Chemistry, 2015)
A new kind of dendritic-salicylaldehydeimine ligand was synthesized using 1.0G polyamidoamine and salicylaldehyde as raw materials through Schiff reaction and further formed dendritic copper complex by Cu complex ion. The structures of dendritic ligand and its copper complex were characterized by elemental analysis, IR, NMR, UV and XRD. With H2O2 as the oxidant, the oxidation reaction performance of dendritic copper complex catalyzing ascorbic acid was determinated by spectrophotometry and catalytic kinetic model was established. The influences of catalytic reaction order, pH value of buffer and complexes concentration on catalytic reaction rate constant were investigated. Results showed that the dendritic copper complex had good mimic enzyme activity. The catalytic reactions had the same features of pseudo-first-order reaction to enzymatic reaction. The catalytic reaction rate obviously imcreased under the conditions of higher concentration of mimic enzyme complex and pH = 7-7.5.